Graft-type polymer electrolyte membranes based on poly(ether ether ketone)/nanosilica hybrid films for fuel cell applications. (2nd November 2016) - Hamada, Takashi; Fukasawa, Hideyuki; Hasegawa, Shin; Miyashita, Atsumi; Maekawa, Yasunari
Abstract: The effect of nanosilica addition on the ionic conductivity, water uptake, and mechanical properties of poly(styrenesulfonic acid)-grafted poly(ether ether ketone) polymer electrolyte membranes (PEEK-PEMs) were investigated using silica-containing PEEK-PEMs (PEM-Si1, -Si3, and-Si5 ) prepared by radiation-induced graft polymerization to nanosilica (1, 3, and 5 wt%)-dispersed PEEK films (PEEK-Si1, -Si3, and-Si5 ).PEEK-Si3 and-Si5 exhibited 10%–50% higher grafting degrees (GDs) compared with those of a silica-free PEEK film.PEM-Si3 and-Si5 showed similar and slightly higher water uptakes in the lower- and higher-relative-humidity (RH) ranges compared with that of the silica-free PEMs. Under the fully humidified condition at 80 °C, PEM-Si3 exhibited the highest tensile strength (TS) (16.4 MPa), which is 1.27 and 1.64 times greater than those of the silica-free PEM and Nafion 212. The membrane electrode assembly (MEA) prepared fromPEM-Si3 with an IEC of 3.30 mmol/g showed a maximum power density of 612 mW/cm 2 under 30% RH, which was 7% higher than that of the silica-free PEM-based MEA. On the basis of the aforementioned results, we concluded that (1) nanosilica was introduced into both hydrophilic (ion channel) and hydrophobic (matrix PEEK) phases in the PEMs; (2) nanosilica in the hydrophilic phase exhibits greater water absorption tendency but not greater water retention character, under high- and low-RH conditions, respectively; and (3) nanosilica in the hydrophobic phase increases the mechanical properties of silica-containing PEMs. Highlights: Nanosilica-containing PEEK-PEMs (PEM-Si) were prepared by radiation grafting. Nanosilica-containing PEEK exhibited higher grafting degrees than silica-free PEEK. PEM-Si exhibited higher tensile strength than silica-free PEM. Nanosilica was introduced into both ion channel and matrix PEEK in the PEMs.